Pengembangan Virtual Tour Berbasis Web untuk Peningkatan Akses Informasi Wisatawan di Desa Wisata Keris Aeng Tong Tong: Development of a Web-Based Virtual Tour to Increase Access to Information for Tourists in the Keris Aeng Tong Tong Tourism Village - Khoironi, Khoironi; Fahrul Hardiansyah, Fadilah; Agustien, Lusiana; Walid Hujairi, Ahmad; Prasetyo, Joko; Fardiansyah Putra, Deny (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
The development of information technology today has made it easier for people to access various types of information quickly and efficiently. One of the rapidly growing innovations is the virtual tour, which enables the interactive presentation of information about a location or place. through a virtual tour, visitors can explore a location and learn about its history or related information, either through a virtual guide or an application. The aeng tong tong keris tourism village, known as a center for keris craftsmanship, has not yet utilized virtual tourtechnology. Therefore, the implementation of this technology is expected to help tourists gain deeper knowledge about the village, including the keris-making process and its cultural heritage. The development of this Virtual Tour uses the MDLC (Multimedia Development Life Cycle) method, which is the most suitable approach for multimedia-based projects. This technology utilizes 360-degree panoramic image capture and integrates it with location data and analysis. Thus, tourists can access comprehensive information virtually